Effects of Artichoke Against Cyclophosphamide-Induced Nephrotoxicity and Oxidative Stress in Rats - Kaya, Emre; Yilmaz, Seval; Colakoglu, Neriman; Kaymaz, Mustafa Bahadır (My University, 2025)
This study was undertaken to investigate how artichokes affects the oxidative stress and nephrotoxicity caused by cyclophosphamide (CP) in rats. The first group, known as control group, was given no medication; second group received artichoke treatment for seven days; third group received a single dose of CP by injection; and fourth group received artichoke treatment for five days following administration of single dose of CP, in addition to seven days of artichoke treatment prior to it. One intraperitoneal dosage of CP (150 mg/kg) was administered and artichoke extract (1 g/kg/day) was given using gavage. GSH level (p?0.001) and CAT (p?0.001) activities were found to be significantly lower in the CP group than in the control group, whereas MDA level (P?0.001), GSH-Px (p=0.002), SOD (p?0.001), and GST (p?0.001) activities were found to be significantly higher. When the CP group was compared with the artichoke+CP group, significant changes were determined in other markers except CAT activity. No statistical difference was observed when the control and only artichoke groups were compared. All values except the MDA level approximated to the control group values when artichoke+CP group was compared to the control group. It was found that the decline in MDA levels was statistically different in the artichoke+CP group compared to the CP group, but the average did not reach the control group values statistically. Histopathologically, in CP group, dilatation in distal tubulin, glomerular atrophy in a few areas and tubulin of foamy appearance were encountered. In CP+artichoke group was observed less frequently dilatation in distal tubule. These findings suggest that unique natural antioxidant artichoke may protect rats from oxidative stress and CP-induced nephrotoxicity.
Keywords: Antioxidant; Cyclophosphamide; malondialdehyde; artichoke